Towards a Multiple Input-Multiple Output paper mill: Opportunities for alternative raw materials and sidestream valorisation in the paper and board industry - Bousios, Spyridon; Worrell, Ernst (Elsevier BV, 2017)
The paper and board industry (PBI) faces a series of challenges, ranging from shifts in the availability and quality of raw materials to the generation of large amounts of sidestreams whose disposal entails significant costs. The concept of the “Multiple Input-Multiple Output (MIMO) Paper Mill” is proposed here as an option for addressing these issues by introducing, on the one hand, flexibility regarding the types of fibre sources that can be used as raw materials and, on the other, a full utilisation of all fractions of the raw materials, including those that were so far considered to be sidestreams of papermaking. With regard to raw material flexibility, researchers have implemented various pretreatment and pulping methods on potential alternative, non-wood, fibre sources for the PBI, which can be found primarily in agro-industrial residues and plants specially cultivated for this purpose. Research on the conversion of various types of papermaking sidestreams into energy and material products has also been extensive, with the new products aimed at (re)use within both the PBI itself and other sectors. Given that technical aspects have gained the most attention so far, more focus should now be placed also on the economic and organisational sides of the concept. It is also crucial to start evaluating integrated MIMO cases, taking into account the interconnected effects that new raw materials have on the papermaking process and its sidestreams, instead of looking into isolated MI and MO examples.
Keywords: Non-wood fibers; Paper; Pulp; Waste management; attention; fiber; human; human cell; paper industry; pulping; scientist; waste management; Taverne